Neonatal and pediatric extracorporeal membrane oxygenation in developing Latin American countries - Javier Kattan; Álvaro González; Andrés Castillo; Luiz Fernando Caneo (Elsevier, 2017)
Objective: To review the principles of neonatal-pediatric extracorporeal membrane oxygenation therapy, prognosis, and its establishment in limited resource-limited countries in Latino America. Sources: The PubMed database was explored from 1985 up to the present, selecting from highly-indexed and leading Latin American journals, and Extracorporeal Life Support Organization reports. Summary of the findings: Extracorporeal membrane oxygenation provides "time" for pulmonary and cardiac rest and for recovery. It is used in the neonatal-pediatric field as a rescue therapy for more than 1300 patients with respiratory failure and around 1000 patients with cardiac diseases per year. The best results in short- and long-term survival are among patients with isolated respiratory diseases, currently established as a standard therapy in referral centers for high-risk patients. The first neonatal/pediatric extracorporeal membrane oxygenation Program in Latin America was established in Chile in 2003, which was also the first program in Latin America to affiliate with the Extracorporeal Life Support Organization. New extracorporeal membrane oxygenation programs have been developed in recent years in referral centers in Argentina, Colombia, Brazil, Mexico, Perú, Costa Rica, and Chile, which are currently funding the Latin American Extracorporeal Life Support Organization chapter. Conclusions: The best results in short- and long-term survival are in patients with isolated respiratory diseases. Today extracorporeal membrane oxygenation therapy is a standard therapy in some Latin American referral centers. It is hoped that these new extracorporeal membrane oxygenation centers will have a positive impact on the survival of newborns and children with respiratory or cardiac failure, and that they will be available for an increasing number of patients from this region in the near future. Resumo: Objetivo: Analisar os fundamentos, prognóstico e estabelecimento da terapia de oxigenação por membrana extracorpórea ECMO neonatal-pediátrica em países da América Latina com recursos limitados. Fontes: A base de dados PubMed foi explorada de 1985 até hoje, selecionando os principais periódicos da América Latina e relatos da Organização de Suporte de Vida Extracorpóreo. Resumo dos achados: A oxigenação por membrana extracorpórea proporciona "tempo" para descanso pulmonar e cardíaco e para recuperação. Ela é usada no campo neonatal-pediátrico como terapia de resgate, com mais de 1.300 pacientes com insuficiência respiratória e cerca de 1.000 pacientes com cardiopatias por ano. Os melhores resultados de sobrevida de curto e longo prazo são de pacientes com doenças respiratórias isoladas, estabelecendo uma terapia padrão em centros de encaminhamento para pacientes de alto risco. O primeiro programa de oxigenação por membrana extracorpórea neonatal/pediátrico na América Latina foi estabelecido no Chile em 2003, que também foi o primeiro programa na América Latina a se afiliar à Organização de Suporte de Vida Extracorpóreo. Novos programas de oxigenação por membrana extracorpórea foram desenvolvidos nos últimos anos em centros de encaminhamento na Argentina, Colômbia, Brasil, México, Peru, Costa Rica e Chile, que atualmente estão fundando a seção da América Latina da Organização de Suporte de Vida Extracorpóreo. Conclusões: Os melhores resultados de sobrevida de curto e longo prazo são de pacientes com doenças respiratórias isoladas. Atualmente, a terapia de oxigenação por membrana extracorpórea é uma terapia padrão em alguns centros de encaminhamento da América Latina. Esperamos que esses novos centros de oxigenação por membrana extracorpórea tenham um impacto positivo sobre a sobrevida de neonatos e crianças com insuficiência respiratória ou cardíaca e que estejam disponíveis para um número cada vez maior de pacientes de nossa região no futuro próximo. Keywords: Extracorporeal membrane oxygenation, ECMO, Respiratory failure, Cardiac failure, Pulmonary hypertension, ELSO, Palavras-chave: Oxigenação por membrana extracorpórea, ECMO, Insuficiência respiratória, Insuficiência cardíaca, Hipertensão pulmonar, ELSO